PENGELOLAAN MANAJEMEN SUMBER DAYA MANUSIA DALAM UPAYA MENINGKATAKAN EFEKTIFITAS KERJA - Nur Faizin, 07.3502.0719; Waruwu, Penunjang (Students Journal of Economic and Management, 2012)
This research is a study that tested the effect of Leadership Styles and Communications Intern for Work Effectiveness Department of Education district office clerk Reban Batang. The population in this study were employees of local public Reban Batang district totaling 44 people, then the results of the research data was tested with the validity and reliability, the result, the whole construct produce valid and reliable values. Further analysis researchers used multiple regression analysis to explain the relationship between these variables. The result is a style of leadership and internal communication have a positive and significant impact on the effectiveness of the work. It can be concluded that if the level of leadership style and high internal communication will produce a high work effectiveness as well. This is consistent with the review of existing theories and the results of an analysis of previous studies. It is expected that the managers and staff of local public school district in order to maintain a level of style reban leadership and internal communications, so that organizational goals can be achieved together. This study has limitations that the sampling period is relatively short, and do not consider the control variables and other key variables. Therefore, further research is suggested to consider the other main variables and control variables as well as the period of the study needs to be longer so that it can be generalized.Key words: Leadership styles, Communications Intern, and work effectiveness.